RESUMO TESE:A SYSTEMS DESIGN APPROACH TO SUSTAINABLE DEVELOPMENT: EMBRACING THE COMPLEXITY OF ENERGY CHALLENGES IN LOW-INCOME MARKETS - Costa Júnior, Jairo da; Diehl, Jan Carel; Snelders, Dirk; Secomandi, Fernando (MIX Sustentável, 2020)
RESUMO TESE